2016
DOI: 10.1016/j.ejca.2016.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival of children and young people with central nervous system embryonal tumours in the North of England, 1990–2013

Abstract: Background: Medulloblastoma and primitive neuroectodermal tumours (PNET) are the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Survival rates in the herein presented consecutive national Norwegian MB/CNS‐PNET material were in line with a similar study from Sweden, but lower than results from other countries (Canada and France) . One possible explanation is that the Canadian work did not include patients from the period 1974–1990.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Survival rates in the herein presented consecutive national Norwegian MB/CNS‐PNET material were in line with a similar study from Sweden, but lower than results from other countries (Canada and France) . One possible explanation is that the Canadian work did not include patients from the period 1974–1990.…”
Section: Discussionsupporting
confidence: 83%
“…Medulloblastoma (MB) and supratentorial primitive neuroectodermal tumor (CNS‐PNET) account for about 15%–20% and 2.5%, respectively, of malignant brain tumors in children. Altogether, these two comprise approximately 10%–15% of all pediatric brain tumors . Both entities are embryonal tumors, MB arising in the infratentorial and CNS‐PNET in the supratentorial brain.…”
Section: Introductionmentioning
confidence: 99%
“…Fairley et al . found an OS of 54% in 5 years for children under 14 years old in the U.K.[6] Similarly, Smoll, in 2012, calculating the cumulative relative survival estimate, found a 5-year OS and 10-year OS of 25%/25% and 56%/52% for infants and children, respectively. [22] The lack of information from Brazilian cohorts does not allow internal comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…This led to a reduction in the risk of death by approximately 30%. [6] Nowadays, current treatment protocols include maximal safe tumor resection followed by radiotherapy in children older than 3 years old, and chemotherapy (CT) with cytotoxic agents, both according to risk stratification. For children under 3 years old, only CT with potent agents is allowed due to the possible damage caused by irradiation on an immature brain.…”
Section: Introductionmentioning
confidence: 99%
“…16 We observed that incidence of CNS tumours increased until 2002 and plateaued thereafter, similar to Australia. 13 Many studies found increases over the entire study period, 8,11,12,17,20 others found no increase, 14,16,19,32,35,42,43 or even a decrease. 35 We also found that incidence of epithelial neoplasms and melanomas increased over the entire study period, similar to the USA, 10,32 Australia, 13 and Korea.…”
Section: International Comparisonmentioning
confidence: 99%